Biomechanical Comparison of Tibial Plateau Leveling Osteotomy Performed With a Novel Titanium Alloy Locking Plate Construct vs. an Established Stainless-Steel Locking Plate Construct - Bleakley, Seth; Palmer, Ross; Miller, Nate; McGilvray, Kirk; Tepic, Slobodan (Frontiers in Veterinary Science, 2021)
A novel canine tibial plateau leveling osteotomy (TPLO) fixation device was recently developed with design features such as titanium alloy (TA) material, distal monocortical screw fixation and a point contact under-surface specifically targeted to reduce surgical site infection rates by ensuring tissue perfusion under the plate. The strength of the novel TPLO construct was compared to that of a predicate stainless steel (SS) locking plate construct with bicortical screws in 16 paired cadaveric canine limbs. The mean loads to failure were 716.71 +/- 109.50N (range 455.69 – 839.69N) and 629.50 +/- 176.83N (range 272.58 - 856.18N) in the TA and SS groups respectively. The average ratio of the loads to failure of the paired specimens was 1.18 (P value 0.031). No failure of the TA constructs involved the distal fixation with monocortical screws. Substantial mechanical equivalence of this novel TA monocortical/bicortical fixation construct to an established SS bicortical screw fixation construct is demonstrated. Clinical investigation of potential merits of this novel TA, monocortical/bicortical locking screw/plate system is now warranted.